Financing specifications production of small and medium enterprises - Ilić Đurđijana; Ilić Slađana (Trendovi u Poslovanju)
Small and medium enterprises and entrepreneurs, especially the production type, represent the most efficient segment of the economy in almost all countries of the world. Individually, these companies make the greatest contribution to increasing employment, gross value added and transport, which is why they are considered the backbone of growth and development of national economies. Their role is particularly significant in transition countries facing high unemployment, low level of economic activity, insufficient competitiveness and lack of investment, and where large inefficient state-owned enterprises are still present. As a stable source of job creation, small and medium-sized enterprises also have an important social function by absorbing labor surpluses in transition processes and ownership transformations of state and social enterprises. The survival, growth and development of manufacturing small and medium enterprises are primarily determined by the possibilities of financing from favorable sources. Limited access to sources of financing both in the money market and in the capital market, especially in terms of price and terms of use, may be the most important feature and biggest problem for these companies. Therefore, the issues of this paper are dedicated to the specificities of financing small and medium-sized enterprises in the production sector in order to improve their financial management and support in making adequate financial decisions.